15d-PGJ2-loaded in nanocapsules enhance the antinociceptive properties into rat temporomandibular hypernociception - Clemente-Napimoga, Juliana T. (2012)
Aims: To verify whether the nanoencapsulation of 15d-PGJ(2) in poly(D,L-lactide-co-glycolide) (PLGA) nanocapsules (15d-PGJ(2)-NC) might potentialize its antinociceptive activity into rats' temporomandibular joint (TMJ).Main methods: Transmission electron microscopy (TEM) and atomic force microscopy (AFM) were used to evaluate the morphology and suspension of the PLGA nanocapsules. Rats were pretreated (15 min) with an intra-TMJ injection of unloaded 15d-PGJ(2) or 15d-PGJ(2)-NC at concentrations of 10, 100 or 1000 pg followed by an ipsilateral intra-TMJ injection of 1.5% formalin. The nociceptive behavioral response was observed during 45 min: animals were then sacrificed and the periarticular tissue was removed for IL-1 beta measurements.Key finding: TEM and AFM analyses showed that 15d-PGJ(2)-NC is spherical without any aggregates or adhesion confirming that this formulation is a good drug carrier system for 15d-PGJ(2). Pretreatment with 15d-PGJ(2)-NC (100 and 1000 pg/TMJ), but not unloaded 15d-PGJ(2), was found to significantly decrease the release of IL-1 beta cytokine and the animals' nociceptive behavioral response induced by intra-TMJ injection of formalin.Significance: The compound 15d-PGJ(2)-NC might be used as a potential antinociceptive and anti-inflammatory agent to treat temporomandibular disorders in clinical practice. (c) 2012 Elsevier B.V. All rights reserved.